Quantification and antibiotic susceptibility of Salmonella spp., Salmonella enteritidis and Salmonella typhimurium in raw vegetables (ulam) - Mohd Shahril, Najwa; Rukayadi, Yaya; Anyi, Ubong; Loo, Yuet Ying; Chang, Wei San; Lye, Ying Ling; Thung, Tze Young; Anuar, Aimi Syazana; Tan, Malcolm Turk Hsern; Goh, Sur Guat; Kuan, Chee Hao; Nakaguchi, Yoshitsugu; et al. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Salmonella has been reported to be presence both in raw and processed foods worldwide. In this study, the prevalence, quantification and antibiotic susceptibility of Salmonella isolated from raw vegetables or locally known as ulam such as asiatic pennywort (Centella asiatica (L) Urb), water dropwort (Oenanthe javanica (Blume) DC), long bean (Vigna sinensis EndL), and winged bean (Psophocarpus tetragonolobus (L) DC) obtained from retail markets in Selangor, Malaysia were carried out. From 96 samples tested, the overall prevalence of Salmonella spp. was 97.9%, Salmonella Enteritidis was 54.2% and Salmonella Typhimurium was 82.3% respectively. Samples were contaminated with Salmonella ranging from <3 to 2400 MPN/g. Salmonella Enteritidis and Salmonella Typhimurium isolates obtained from the raw vegetables (ulam) were found to exhibit high resistance against ampicillin (100%), erythromycin (100%), amoxicillin/clavunic acid (81.3%), cephalothin (75%), streptomycin (50%) and ciprofloxacin (50%). All Salmonella isolates showed multi drug resistant (MDR) profile with each isolate being resistant to 3 or more antibiotics. The multiple antibiotic resistance (MAR) index of Salmonella isolates ranged from 0.27 to 0.55 for Salmonella Enteritidis and 0.27 to 0.82 for Salmonella Typhimurium. The presence of Salmonella on raw vegetables (ulam) and high antibiotic resistance isolates indicated that raw vegetables could be contaminated and thus imposes possible health risk to local consumers.